(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Lupus nephritis is a common and severe manifestation of systemic lupus erythematosus that can lead to end-stage renal disease and death. The aim of this study was to compare the efficacy and safety of mycophenolate mofetil (MMF) and cyclophosphamide as induction therapy and subsequently as maintenance therapy for lupus nephritis. Materials and Methods. In this retrospective case-control study, 67 patients with proliferative lupus nephritis who were treated with MMF (n = 45) and pulse of intravenous cyclophosphamide (n = 22) were included. Remission of the kidney disease, mortality, and adverse events were evaluated and compared between the two groups. Results. The 45 patients treated with MMF had a mean age of 33.8 ± 10.6 years and 17.1% of them were males. The 22 patients treated with pulse of intravenous cyclophosphamide had a mean age of 38.1 ± 11.1 years and 18.2% of them were males. Complete and partial kidney remission occurred in 40% and 42.2% of the patients treated with MMF and in 31.8% and 59.1% of the patients treated with cyclophosphamide, respectively. No significant differences were observed in complete and partial remission between the two groups. No mortality was reported in the studied patients. There were no significant differences in the frequency of adverse events between the two groups. Conclusions. The efficacy of MMF in long-term treatment of lupus nephritis was comparable to that of cyclophosphamide, and there is no significant differences in the rate of side effects between the two regimens.